Simple Starch Modification Using Physical, Chemical and Combined Physical and Chemical Methods to Produce Pre-cooked Flour Rich in Resistant Starch Made of Corn, Potato and Cassava - Wulan, Siti Narsito; Saparianti, Ella; Widjanarko, Simon B.; Kurnaeni, Nina (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The research was conducted to evaluate a resistant starch formation in pre-cooked flour made of various native starches using different method of precooking. The raw materials used as the source of native starches were corn, potato and cassava. The types of respective treatment were the physical method, i.e. boiling the raw materials followed by cooling at 4ËšC; the chemical modification was carried out by boiling the raw materials in Ca(OH)2 solution; and the combined method of physical and chemical which was performed by boiling the raw materials in Ca(OH)2 solution then cooling at 4ËšC.Â Each treatment was aimed to produce a specific effect on the starch, i.e.Â To promote retro gradation (the physical method), cross-linking (the chemical modification), and the both of them (the combined method). The treated samples were then dried and milled to obtain the pre-cooked flour. The results showed that the method of pre-cooking affected the chemical composition of the individual corn, potato, and cassava flours. The degree of resistant starch formed varied with the raw materials as well as the method of pre-cooking. The combined method of physical and chemical pre-cooking applied on the corn starch produced the highest level of resistant starch (9.98%). Key words:Â resistant starch, starch modification, pre-cooking treatment, cross-linking